Strategy For Improving The Quality Of Education In Schools - Maulidiyah, Hikmatul (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2024)
The quality (quality) of education has always been something that must be strived for by all elements of education. Therefore, managing an educational institution must be comprehensive and integrated. This is inseparable from how an institution manages that quality. The quality of education can be seen from the fulfillment of the eight educational standards that must be met by schools. The strategy for improving the quality of education must be directed at the components that determine the quality of education in schools, namely: 1) Strengthening Leadership in Schools, 2) Good curriculum management, 3) Increasing the Professionalism of Teachers and Education Personnel, 4) Complete facilities and infrastructure, 5) The creation of good relations with the surrounding community, 6) Continuous evaluation/improvement. By achieving a quality education process, it is ensured that it can also produce quality output by the National Education Standards.